The Mayan codices, Fray Diego de Landa, the colonial Mayan literature and the recent history of the decipherment of the Mayan hieroglyphs - Solórzano Fonseca, Juan Carlos (2022)
During the 16th century, Spaniards in Yucatán found a significant number of codices, or pieces of rough materials worked to produce the Mayan manuscripts. Most of these writings were burnt by Fray Diego de Landa, but before proceeding with their final destruction, he transcribed the necessary amount of information that centuries later gave Yuri K. Knórozov the clues to decipher the Mayan hieroglyphs. Throughout Spanish dominion, the Maya learned how to write its own language using the Latin alphabet while they forgot its own scripture system. At the beginning of the 19th century a large number of Mayan ruins of ancient cities were discovered, and soon Scholars started to wonder how to read the inscriptions sculpted in its monuments. This did not would occurred until the middle of the 20th century, when Knórozov discover the way to understand Mayan hieroglyphs.